2023
DOI: 10.1097/ju.0000000000003209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pharmacotherapy for Overactive Bladder on the Incidence of and Factors Related to Urinary Tract Infection: A Systematic Review and Meta-analysis

Abstract: The aim of this meta-analysis was to investigate the effect of pharmacotherapy for overactive bladder on the pathogenesis of urinary tract infection. Materials and Methods: A comprehensive search was performed in MEDLINE and the Cochrane Library using terms for overactive bladder, antimuscarinic agents, and beta 3eadrenoceptor agonists. The primary end point was the emergence of urinary tract infection after pharmacotherapy for overactive bladder. The secondary end point was the emergence of urinary retention,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
(63 reference statements)
0
7
1
1
Order By: Relevance
“…Ultimately, 4 randomized, double-blind, placebo- and antimuscarinic agent–controlled trials, which are “ideal, more reliable, head-to-head direct comparisons between antimuscarinics and β 3 -adrenoreceptor agonists,” did not show any significant increase in the incidence of treatment-emergent UTIs, 2,4,5,8 contrary to the claimed conclusion by Tsubouchi et al 1 For these reasons we are not in agreement with the authors’ conclusion.…”
contrasting
confidence: 81%
See 1 more Smart Citation
“…Ultimately, 4 randomized, double-blind, placebo- and antimuscarinic agent–controlled trials, which are “ideal, more reliable, head-to-head direct comparisons between antimuscarinics and β 3 -adrenoreceptor agonists,” did not show any significant increase in the incidence of treatment-emergent UTIs, 2,4,5,8 contrary to the claimed conclusion by Tsubouchi et al 1 For these reasons we are not in agreement with the authors’ conclusion.…”
contrasting
confidence: 81%
“…To the Editor: The authors performed an elegant meta-analysis and concluded, “This meta-analysis showed that antimuscarinic agents statistically significantly increased the incidences of urinary tract infection (UTI) and lower urinary tract symptoms and dysfunction, but β 3 -adrenoceptor agonists did not.” 1 They note “direct comparisons between antimuscarinics and β 3 -adrenoreceptor antagonists by using only head-to-head [randomized controlled trial] data would be ideal, more reliable, and more informative.” However, they failed to note that in the best existing comparator of the therapies, a single randomized study by Abrams et al (which was referenced in their paper), 2 the comparisons between placebo (3.7% in 81 patients), mirabegron 25 mg (1.3% in 77 patients), mirabegron 50 mg (2.6% in 78 patients), and solifenacin 5 mg (2.6% in 156 patients) do not support their conclusion (see Table). Similarly, the SYNERGY II study, a randomized, multicenter, phase 3 study comparing the long-term safety and efficacy of mirabegron 50 mg and solifenacin 5 mg in combination with monotherapy, reported no significant difference in the incidence of treatment-emergent UTIs between mirabegron 50 mg (6.2% in 305 patients) and solifenacin 5 mg (5.9% in 303 patients), but slightly increased rates of UTI in the combination group (8.4% of 1,206 patients).…”
mentioning
confidence: 99%
“…To the Editor: We express our gratitude to Ritter et al for their valuable remarks on our study. 1 They acknowledged the significance of our findings and emphasized the need for investigating individual outcomes associated with pharmacotherapy for overactive bladder syndrome (OAB). However, they also identified certain limitations in our study.…”
mentioning
confidence: 88%
“…As we explained in the discussion section of our paper, out of the 33 trials included in the meta-analysis, some studies reported secondary outcomes such as urinary retention, increased residual urine volume, and dysuria, while others did not. 1 Consequently, the number of papers examining secondary outcomes was lower than those assessing primary outcomes. Furthermore, there was heterogeneity in the definitions of secondary end points across the papers, which may have led to inconsistent evaluation of lower urinary tract symptoms and dysfunction in the context of pharmacotherapy.…”
mentioning
confidence: 99%
“…To the Editor: We read with great interest the article by Tsubouchi et al 1 We found the results of this study to be of great importance and believe that they highlight the need of researching the individual outcomes related to pharmacotherapy of overactive bladder syndrome (OAB). The study found that antimuscarinic agents increased the incidence of urinary tract infections (UTIs), lower urinary tract symptoms, urinary retention, and post-void residual volume, while beta-3 adrenoceptor agonists did not, therefore concluding that it may be safer to use beta-3 adrenoceptor agonists to prevent the emergence of UTIs.…”
mentioning
confidence: 90%